2003
DOI: 10.1016/s0735-1097(03)00312-7
|View full text |Cite
|
Sign up to set email alerts
|

Immediate results and one-year clinical outcome after percutaneous coronary interventions in chronic total occlusions

Abstract: Successful PCI was achieved in a high percentage of CTOs with a low incidence of complications. At one-year follow-up, patients with successful PCI of a CTO had a significantly better clinical outcome than those whose PCI was unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
283
10
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(323 citation statements)
references
References 29 publications
19
283
10
11
Order By: Relevance
“…Several previous observational studies and meta‐analysis regarding clinical outcomes in patients with successful CTO PCI have demonstrated its beneficial effect, such as improved survival rates and LV function, compared with failed PCI 1, 4, 5, 6, 8, 15. In contrast, some observational studies suggest that successful CTO PCI is not associated with improvement of survival rates and cardiovascular events 16, 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous observational studies and meta‐analysis regarding clinical outcomes in patients with successful CTO PCI have demonstrated its beneficial effect, such as improved survival rates and LV function, compared with failed PCI 1, 4, 5, 6, 8, 15. In contrast, some observational studies suggest that successful CTO PCI is not associated with improvement of survival rates and cardiovascular events 16, 17.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that successful CTO intervention was associated with improved survival rates and angina symptom relief when compared with the failed CTO intervention 1, 4, 5, 6. Despite previous study results, the proportion of patients who underwent PCI for CTO lesions was still lower,7, 8 and current guidelines recommend that the physicians should consider the clinical benefits regarding clinical, angiographic, and technical parameters when determining whether or not to perform PCI in patients with CTO lesions 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Although the treatment of CTO remains a technical challenge and still 20-35% of CTOs are not recanalized by percutaneous coronary intervention (PCI) even when performed by experienced operators, 3,4) successful PCI for CTO has been shown to improve left ventricular (LV) systolic function, reduce angina, increase exercise capacity, and reduce the need for late bypass surgery. 3,5,6) On the other hand, CTO patients who were not revascularized had a significantly higher rate of cardiac mortality and sudden cardiac death compared with those who were revascularized. 7,8) Moreover, in acute myocardial infarction (AMI) patients, the presence of CTO in a non-infarct-related artery (IRA) is a strong and independent risk factor for short-and middle-term mortality.…”
Section: Oronary Chronic Total Occlusion (Cto) Is Commonlymentioning
confidence: 99%
“…Vol 56 No 6 CHRONIC TOTAL OCCLUSION quiring extracorporeal membrane oxygenator (n = 12), and patients presenting with poor left ventricular function (LVEF < 40%) after successful PCI (n = 52) were excluded. The remaining 353 patients were divided into two groups; patients with CTO (n = 25) and those without CTO (n = 328), and clinical indices including patient demographics, clinical and angiographic characteristics, and in-hospital and 30-day outcomes were compared.…”
Section: Oronary Chronic Total Occlusion (Cto) Is Commonlymentioning
confidence: 99%
“…1)2) In addition, several randomized trials have demonstrated that stent implantation decreases the rate of restenosis and reocclusion [3][4][5][6][7][8][9] and confers a long-term survival advantage. 10) However, restenosis had remained the major complication that has limited the late outcome after PCI prior to the introduction of drug-eluting stents (DESs). Since 2002, DES has been available in Asian countries and there have been several reports about the efficacy of DESs for the reduction of restenoais after DES implantation, and the reports have described a dramatic reduction of restenosis [11][12][13][14][15] as compared with the use of bare metal stents (BMSs).…”
Section: Introductionmentioning
confidence: 99%